Alternatives to neoliberal peacebuilding and statebuilding in Africa - Bereketeab, Redie (Abingdon, Oxon ; New York, N.Y. : Routledge, 2021)
"This book critically interrogates the neoliberal peacebuilding and statebuilding model, instead proposing a popular progressive model centred around the lived realities of African societies. The neoliberal interventionist model assumed prominence and universal hegemony following the demise of state socialism at the end of the Cold War. However, this book argues that it is a primarily short-term, top-down approach that imposes Western norms and values on conflict and post-conflict societies. By contrast, the popular progressive model espoused by this book is based on stringent examination and analysis of the reality of the socio-economic development, structures, institutions, politics and cultures of developing societies. In doing so, it combines bottom-up and top-down, popular and elite, and long-term evolutionary processes of societal construction as a requisite for enduring peacebuilding and statebuilding. By comparing and contrasting the dominant neoliberal peacebuilding and statebuilding model with a popular progressive model, the book seeks to empower locals (both elites and masses) to sit in the driver's seat and construct their own societies. As such, it is an important contribution to scholars, activists, policymakers, civil society organisations, NGOs and all those who are concerned with peace, stability and development across Africa and other developing countries"--
Introduction: Understanding Peace-building and State-building in the Era of Neoliberalism -- Neoliberal Peace-building and State-building -- Popular Progressive Peace-building and State-building -- State Emancipation and Societal Pacification as Prerequisites of Peace-building and State-building -- Peace-building and State-building: Harmony and Discordance -- Conclusion: Summary and Highlights.
"Routledge focus".
OCLC-licensed vendor bibliographic record.
Keywords: Peace-building -- Africa; Nation-building -- Africa; Economic development -- Africa; Self-determination, National -- Africa; POLITICAL SCIENCE / Peace